A Semi‐Mechanistic Population Pharmacokinetic Model of Nusinersen: An Antisense Oligonucleotide for the Treatment of Spinal Muscular Atrophy. (16th August 2018) - Biliouris, Konstantinos; Gaitonde, Puneet; Yin, Wei; Norris, Daniel A.; Wang, Yanfeng; Henry, Scott; Fey, Robert; Nestorov, Ivan; Schmidt, Stephan; Rogge, Mark; Lesko, Lawrence J.; Trame, Mirjam N.
Abstract : A pharmacokinetic (PK) model was developed for nusinersen, an antisense oligonucleotide (ASO) that is the first approved treatment for spinal muscular atrophy (SMA). The model was built with data from 92 nonhuman primates (NHPs) following intrathecal doses (0.3–7 mg) and characterized the PK in cerebrospinal fluid (CSF), plasma, total spinal cord, brain, and pons. The estimated volumes were 13.6, 937, 4.5, 53.8, and 2.11 mL, respectively. Global sensitivity analysis demonstrated that the CSF‐to‐plasma drug distribution rate (0.09 hour −1 ) is a major determinant of the maximum nusinersen concentration in central nervous system (CNS) tissues. Physiological age‐based and body weight‐based allometric scaling was implemented with exponent values of −0.08 and 1 for the rate constants and the volume of distribution, respectively. Simulations of the scaled model were in agreement with clinical observations from 52 pediatric phase I PK profiles. The developed model can be used to guide the design of clinical trials with ASOs.